Preparation of KLa(MoO4)2:Er3+/Yb3+ Phosphors by Cyclic Microwave-Modified Sol-Gel Method and Their Upconversion Properties - Al-Taweel, S.S. (Asian Journal of Chemistry, 2014)
The double molybdate KLa1-x(MoO4)2:Er3+/Yb3+ phosphors with the doping concentrations of Er3+ and Yb3+ (x = Er3+ + Yb3+, Er3+ = 0.05, 0.1, 0.2 and Yb3+ = 0.2, 0.45) were successfully synthesized by a cyclic microwave-modified sol-gel method and the upconversion properties have been investigated. Well-crystallized particles were formed after heat treatment at 900 °C for 16 h, showing a fine and homogeneous morphology with particle sizes of 2-5 μm. Under excitation at 980 nm, the synthesized particles exhibited a strong 525 nm emission band and a weak 550 nm emission band in the green region and a weak 655 nm emission band in the red region. The Raman spectra of the particles indicated the strong peaks at higher frequencies and weak peaks at lower frequencies.